Acquired platelet storage container leaks and contamination with environmental bacteria: A preventable cause of bacterial sepsis. Issue 3 (20th December 2021) - Gammon, Richard R.; Reik, Rita A.; Stern, Marc; Vassallo, Ralph R.; Waxman, Dan A.; Young, Pampee P.; Benjamin, Richard J.
Abstract: Background: Apheresis platelets (AP) may be contaminated by environmental bacteria via container defects acquired during processing, transport, storage, or transfusion, as highlighted by a recent series of septic reactions related to Acinetobacter spp. and other bacterial strains. Study design and methods: The frequency and nature of acquired container defect reports to one manufacturer were evaluated from January 2019 to July 2020. The published incidence of contamination and sepsis due to environmental bacteria with culture screened AP in the United States was reviewed for the period of 2010–2019. Results: Review of a manufacturers' records showed 23 US reports of leaks involving 24 containers attributed to postmanufacturing damage, at a rate of 44 per million distributed storage containers. Analysis of returned containers showed evidence of scratches, impressions, and/or piercings. Literature review of US hemovigilance data revealed that environmental bacteria comprised 7% of confirmed positive primary bacterial culture screens, were responsible for 14%–16% of reported septic, and 8 of 28 (29%) fatal reactions with bacterial‐culture screened AP. Sepsis cases have been reported with culture screened, point‐of‐issue (POI) tested, or pathogen‐reduced AP. Discussion: Environmental contamination of AP is rare but can cause sepsis. Container damage provides a pathway for contamination after culture screening, POI bacteria testing, or pathogen reduction. Blood collectors and transfusion services should have procedures to ensure proper inspection, handling, storage, and transport of AP to avoid damage and should enhance efforts to detect defects prior to release and to eliminate bacteria from all contacting surfaces to minimize the risk of contamination.